2014
DOI: 10.3177/jnsv.60.420
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Lifestyle Factors Associated with Vitamin D Status in Pregnant Japanese Women

Abstract: Vitamin D has drawn attention as a significant nutrient to prevent pregnancy complications and health problems in offspring (1, 2). For instance, maternal vitamin D deficiency has been speculated to cause endothelial dysfunction, a key feature of preeclampsia, through a proinflammatory response and increase in oxidative stress (3). Its deficiency also leads to low birth size through the inhibition of bone mineral accrual of the fetus (4).Maintaining maternal circulating 25-hydroxyvitamin D (25(OH)D) concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
3
20
2
1
Order By: Relevance
“…Only one in three women in the study were taking dietary supplements containing vitamin D, such as multivitamins and calcium supplements enriched with vitamin D. Intake of supplements containing vitamin D significantly lowered the risk of vitamin D deficiency in the bivariate model but was no longer significant in the multivariate model. This finding was inconsistent with previous studies conducted among pregnant Japanese [32] and Chinese [38] women, in which the use of vitamin D supplements and multivitamins were associated with higher serum 25(OH)D levels. One of the possible explanations for these findings is that the use of vitamin D supplements was uncommon among Malaysian pregnant women.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Only one in three women in the study were taking dietary supplements containing vitamin D, such as multivitamins and calcium supplements enriched with vitamin D. Intake of supplements containing vitamin D significantly lowered the risk of vitamin D deficiency in the bivariate model but was no longer significant in the multivariate model. This finding was inconsistent with previous studies conducted among pregnant Japanese [32] and Chinese [38] women, in which the use of vitamin D supplements and multivitamins were associated with higher serum 25(OH)D levels. One of the possible explanations for these findings is that the use of vitamin D supplements was uncommon among Malaysian pregnant women.…”
Section: Discussioncontrasting
confidence: 98%
“…In this study, pregnant women who had higher intake vitamin D were more likely to have lower risk of vitamin D deficiency. This finding is in agreement with Shiraishi et al [32] that found higher vitamin D intake significantly contributed to higher serum 25(OH)D concentration among pregnant women. This could be attributed to the high consumption of vitamin D containing food such as milk and milk products and fish and fish products (as shown in Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, women in Malaysia tend to reduce sunshine exposure due to covered dress (religious practice) or use of sunscreen for either cosmetic reasons or to prevent skin damage [38,39]. The use of sunscreen could block UV light and subsequently inhibit vitamin D production [40]. Moreover, nearly all (98%) pregnant women in the present study were housewives and indoor workers (data not shown), which could contribute to them having a lower duration of sun exposure.…”
Section: Discussionmentioning
confidence: 75%
“…Being primigravida was associated to a lower mean of concentration of vitamin D, a higher percentage of hypovitaminosis D and a lower percentage of vitamin D sufficiency, which was in agreement with the results from other authors. 20,[23][24][25] Pregnant adolescents had a higher percentage of hypovitaminosis D. Perhaps pregnant adolescents may tend to be more withdrawn and participate in fewer outdoor activities or even have less adherence to prenatal recommendations. Studies have shown that this age group seems to be more vulnerable to vitamin D deficiency.…”
Section: Variablesmentioning
confidence: 99%